Physiological predictors of distance runners` performance: a narrative review - Grivas, G. (Trends in Sport Sciences, 2020)
The main purpose of this article was to review and discuss the current literature on the following physiological parameters: maximal oxygen uptake (VO2max), running economy (RE), running velocity at vVO2max (vVO2max), time limit at vVO2max (tlimit), running velocity at lactate threshold (vLT) and maximal speed (Vmax) on running performance. Many coaches and trainers believed that athletes with higher VO2max have better performance, but a lot of studies have shown that VO2max is a poor predictor of endurance performance. Alternatively, RE, vVO2max, tlimit, vLT and Vmax were shown to be superior predictors of distance running performance. Therefore, if researchers and coaches can improve the values of all five parameters, the calculations suggested that the runner would be able to complete a marathon in 1:57:58. In conclusion, this review provides some practical suggestions as how to improve the performance in distance runners.